Low-Temperature Magnetic Resonance Imaging with 2.8 μm Isotropic Resolution - Chen, Hsueh-Ying (J Magn Reson, 2017)
We demonstrate the feasibility of high-resolution (1)H magnetic resonance imaging (MRI) at low temperatures by obtaining an MRI image of 20 μm diameter glass beads in glycerol/water at 28 K with 2.8 μm isotropic resolution. The experiments use a recently-described MRI apparatus (J. Magn. Reson., vol. 260, pp. 1–9, 2015) with minor modifications. The sample is contained within a radio-frequency microcoil with 150 μm inner diameter. Sensitivity is additionally enhanced by paramagnetic doping, optimization of the sample temperature, three-dimensional phase-encoding of k-space data, pulsed spin-lock detection of (1)H nuclear magnetic resonance signals, and spherical sampling of k-space. We verify that the actual image resolution is 2.7 ± 0.3 μm by quantitative comparisons of experimental and calculated images. Our imaging approach is compatible with dynamic nuclear polarization, providing a path to significantly higher resolution in future experiments.